DISMANTLING THE MEANING OF LOVE: A DECONSTRUCTION IN THE NOVEL CINTA TERAKHIR BY VINCENTIUS J. BOEKAN - Vincentius Mauk; Nadya Afdholy (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2020)
This study aims to deconstruct the meaning of love in the novel Cinta Terakhir by Vincentius J. Boekan. The novel Cinta Terakhir by Vincentius J. Boekan tells the romance of two human beings, Armando and Rosalia whose meaning is different from love in general. The method used in this research is descriptive qualitative. The results showed that (1) the main character of Armando was a betrayer of love who appeared when Indonesian political conditions were influenced by international politics, then Armando's characters betrayed their love by choosing the NKRI ideology as a fixed price, (2) the nature of patriotism was so inherent in the character's characteristics Armando is very strong towards the ideology of the Republic of Indonesia so Armando prefers to flee with hundreds of thousands of East Timorese people to the West Timor of the Republic of Indonesia and leaves his beloved wife and only daughter in Timor Leste, but Catholic marriage remains husband and wife until death separates.